E-Book selection practises and initiatives planning towards return on investment in Malaysian academic libraries : moving into patron-driven acquisition / Che Zainab Haji Abdullah - Abdullah, Che Zainab (Institute of Graduate Studies, UiTM, 2014)
This study investigates the e-book selection practices pertaining to patrondriven acquisition and library’s initiatives planning on providing e-book services toward return on investment in selected Malaysian academic libraries. This research employs a concurrent mixed-method through semi structured interviews and a survey. Ten experienced acquisition librarians informed in this interview. The qualitative data were transcribed and analysed manually. The common purchasing models of e-book in Malaysian academic libraries are subscription, packages, pick and choose and one-time purchase. None of the libraries adopts the patron-driven acquisition model as being investigated. The questionnaire used as an instrument in a quantitative approached to determine librarian perception on common e-book selection practices (resource sharing, accessibility, support distance education, sustainability, collection features, cataloguing e-structure and user friendliness) and library initiatives planning (technical support, personnel and training). The relationship between e-book selection practices, library initiatives planning and return on investment was further examined.